2019
DOI: 10.1088/1757-899x/546/2/022021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Phragmites australis and Eichhornia crassipes in the removal of high total phosphorus concentrations from water

Abstract: In order to evaluate the accumulation of high phosphorus and the distribution on macrophytes part, the experiment was conducted by arranged vegetated and unvegetated treatment in a greenhouse experiment. Reactor containing 5L of phosphorus solution (50 or 500 mg/L), 4 kg of sediment and plants (Phragmites australis or Eichhornia crassipes) were prepared. The studied concentrations tried to stimulate an accumulation of Total Phosphorus (TP) in plants. Water were sampled every 5 days during 30 days of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…in the Hula Valley prior to its drainage, although they had not been among the dominant taxa (Avisar & Fox, 2012;Dimentman et al, 1992;Gophen, 2000). All three are known to grow rapidly and to tolerate elevated phosphorus levels (e.g., Emery & Perry, 1996;Galal et al, 2021;Salamah et al, 2019). The particularly high tolerance of P. australis ("common reed") to increased nutrient and toxic heavy metal loads, and its capacity to accumulate large amounts of both in its tissue, has led to its extensive use in phytoremediation practices in wetlands, especially for controlling phosphorus concentrations (e.g., Ahmad et al, 2014;Carricondo et al, 2020;Srivastava et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the Hula Valley prior to its drainage, although they had not been among the dominant taxa (Avisar & Fox, 2012;Dimentman et al, 1992;Gophen, 2000). All three are known to grow rapidly and to tolerate elevated phosphorus levels (e.g., Emery & Perry, 1996;Galal et al, 2021;Salamah et al, 2019). The particularly high tolerance of P. australis ("common reed") to increased nutrient and toxic heavy metal loads, and its capacity to accumulate large amounts of both in its tissue, has led to its extensive use in phytoremediation practices in wetlands, especially for controlling phosphorus concentrations (e.g., Ahmad et al, 2014;Carricondo et al, 2020;Srivastava et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…nigriventer DNA in the water had been present in the Hula Valley prior to its drainage, although they had not been among the dominant taxa (Avisar & Fox, 2012; Dimentman et al, 1992; Gophen, 2000). All three are known to grow rapidly and to tolerate elevated phosphorus levels (e.g., Emery & Perry, 1996; Galal et al, 2021; Salamah et al, 2019). The particularly high tolerance of P .…”
Section: Discussionmentioning
confidence: 99%
“…Ideal plants for phytoremediation should possess characteristics such as high biomass, a robust root system, fast growth, microbial support, and ease of cultivation. Common reeds, like Phragmites australis, are known for their effectiveness in removing nitrogen and phosphorus from wastewater, thanks to their extensive root system [6]. Studies have demonstrated successful treatment of sewage water with vetiver in a hydroponic system, resulting in over 90% reduction.…”
Section: Introductionmentioning
confidence: 99%